The excited state antiaromatic benzene ring: a molecular Mr Hyde?. (21st September 2015) - Papadakis, Raffaello; Ottosson, Henrik
<x xml:space="preserve">Abstract</x> Baird's rule tells that benzene is an antiaromatic "Mr Hyde" in its lowest excited states, explaining many photoreactions of benzene derivatives.